Historical Approach In LGBT Behavior: Ibrah The Story Of Prophet Luth In The Qur'an Against The LGBT Phenomenon - Nisa Afrinauly Nabila; Neo Fadly (al-Afkar, Journal For Islamic Studies, 2024)
This research is motivated by the author's interest in the LGBT phenomenon that is rampant and becomes a conversation as a form of deviation that is still a pro-contra. LGBT behavior is inseparable from the history of the Prophet Luth with the shamans who are known as same-sex lovers. Through a historical approach, researchers try to explore the LGBT behavior. This research is a type of library research, which in the data collection method uses a way to identify and collect library materials and sources that are certainly relevant to this discussion. Researchers used the method of collection by means of documentation, which is research that uses data by analyzing document data, especially in the form of data sources from a number of literature relevant to the focus of the study. The method of data analysis in this study is the analysis of the references listed. The result of this study is to determine the behavior of LGBT or same-sex attracted behavior through a historical approach. If examined LGBT behavior has started since the time of the Prophet Luth (Bani Shadam). In Indonesia, LGBT behavior is also contrary to Pancasila and the 1945 Constitution and Law No. I Year 1974.